Family in Uzbekistan and its demographic state - Djumavaevna, Tillakhodjaeva Khurshida; Niyatovich, Inatov Murod (The journal of contemporary issues in business and government, 2021)
The article analyzes the population census process and various civil statuses in cities and regions of Uzbekistan since the beginning of the XX century, and also develops appropriate proposals and recommendations. It is analyzed that the marriages and divorces number among the population leads to many changes in socio-economic life and demographic processes that affect its number - fertility, death and natural growth, total fertility, marriages and divorces, maternal and child death. In general, the dynamics indicators of civil status in Uzbekistan serve as the most important factor in studying the social inequality consequences in society.